99mTc tetrofosmin myocardial perfusion scintigraphy in CAD - Pirich, C.; Keinrath, P.; Rettenbacher, L.; Rendl, G.; Holzmannhofer, J.; Hammerer, M.; Schuler, J.; Beheshti, M. (Nuklearmedizin - NuclearMedicine, 2014)
Aim: Early stress imaging (15 min after injection of the radiopharmaceutical) in 99mTc tetrofosmin myocardial perfusion scintigraphy (MPS) has been shown feasible in comparison to standard imaging after 45 minutes, but the effects on image quality and diagnostic accuracy ask for further evaluation. Patients, methods: 97 patients (61 men, 36 women, age 69 ± 11 years) underwent both early (EA) and standard (SA) acquisition (after 14 ± 4 min and 43 ± 6 min, respectively) using 99mTc tetrofosmin gated SPECT with iterative reconstruction. sub- diaphragmatic tracer activity and image quality was scored in a 4-point scale by blinded observers. Semiquantitative myo- cardial perfusion analysis was performed on a 17-segment model using standard cardiac quantification SPECT software (4 DM- SPECT). Stenoses of indeterminate haemody- namic significance were validated by measurement of fractional flow reserve (FFR). Results: Extra-cardiac tracer activity was more commonly found in EA (43%) than in SA (38%), but without any diagnostic impact in > 95% of the patients. The mean summed stress score was significantly higher for early than standard imaging (6.4 ± 6.3 vs.5.6 ± 6.1, p = 0.009). The amount of ischaemic area was not significantly different (EA: 9.1 ±6.7 % vs. SA: 7.8 ± 6.9 %). The mean stress ejection fraction was 52 ± 11% (EA) compared to 55 ± 11 % (SA) (p = ns). FFR was inversely related to SDS at early (r = -0.704, p < 0.05) and standard (r=-0.678, p < 0.05) acquisition. All patients with a FFR < 0.8 (considered as hemodynamically significant stenoses) revealed a positive scan. Conclusion: Stress 99mTc tetrofosmin MPS with early acquisition is feasible and at least equally accurate when iterative reconstruction is applied.
Keywords: Myocardial perfusion scintigraphy; 99mTc tetrofosmin; early acquisition; fractional flow reserve; coronary artery disease